2014
DOI: 10.1017/s0143814x14000038
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal federalism and American exceptionalism: why is there no federal equalisation system in the United States?

Abstract: This article addresses the absence of a federal equalisation programme in the United States, which is a significant aspect of “American exceptionalism”. Comparing the United States with Australia and Canada, we argue that three factors are relevant when accounting for this absence. On one hand, we turn to two societal factors to explain why there was never much political appetite for the creation of a stand-alone equalisation programme in the United States, namely the lack of a direct threat to the territorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…30 As a result, decision-making power for adaptation on the California coast is far more decentralized than in many other cases, with more powers attached to lower levels. 76 Likewise, the central German government has fostered a soft national strategy relevant to adaptation on the German North Sea coast that has been developed in a consultative mode with the states (the Lander), the European Union, and other adjacent European countries. The Lander shares responsibility with the national government for decision-making and delivery in this arena but is reluctant to take over new and additional tasks without sufficient compensation for associated expenditures.…”
Section: Power By Designmentioning
confidence: 99%
“…30 As a result, decision-making power for adaptation on the California coast is far more decentralized than in many other cases, with more powers attached to lower levels. 76 Likewise, the central German government has fostered a soft national strategy relevant to adaptation on the German North Sea coast that has been developed in a consultative mode with the states (the Lander), the European Union, and other adjacent European countries. The Lander shares responsibility with the national government for decision-making and delivery in this arena but is reluctant to take over new and additional tasks without sufficient compensation for associated expenditures.…”
Section: Power By Designmentioning
confidence: 99%
“…Indeed, decades of research on federalism, decentralisation, and international relations have shown that even in the presence of strong systems, horizontal and vertical cooperation is difficult. 76,109,110 Rather, we argue that it is critical to understand how different actors mobilise power and authority in polycentric systems in order to bring about transformational change.…”
Section: Conclusion and Future Contributions Of A Power-centered Framentioning
confidence: 97%
“…32 As a result, decision-making power for adaptation on the California coast is far more decentralised than in many other cases, with more powers attached to lower levels. 76 Likewise, the central German government has fostered a soft national strategy relevant to adaptation on the German North Sea coast that has been developed in a consultative mode with the states (the Lander), the European Union, and other adjacent European countries. The Lander shares responsibility with the national government for decision-making and delivery in this arena but is reluctant to take over new and additional tasks without sufficient compensation for associated expenditures.…”
Section: Power By Designmentioning
confidence: 99%
“…net contributors) should be opposed. This prediction, however, is faced with the counter-argument that the very raison d'être of federations is unity in diversity, solidarity, and crossregional support (Burgess 2006: p. 258;Béland and Lecours 2014). In other words, if fiscal equalisation is the price to pay for keeping the polity together and for allowing compatriots living in relatively deprived regions to enjoy similar public services (Watts 2008: p.…”
Section: Introductionmentioning
confidence: 99%